Corneal Astigmatism in cataract surgery candidates - Ladeveze,Emilio Raúl (2018)
Abstract Purpose: To report the prevalence and analyse corneal astigmatism patterns in cataract surgery candidates. Methods: Researchers examined 2136 eyes from 1204 patients for cataract surgery from 1 January to 31 December 2016. All the candidates were evaluated with partial coherence interferometry (IOLMaster). The results were analysed statistically in relation to qualitative and quantitative variables. Results: The mean age of the patients was 71.9 years with a female predominance. Mean corneal astigmatism was 1.0 dioptre (D). Against the rule (ATR) astigmatism increased with age. Women presented with steeper corneas than men. In those patients who had both eyes measured, we found strong correlations between amount of right and left eye astigmatism, axis and keratometry. Overall, 39% of the eyes had corneal astigmatism > 1.00 D and 19% >1.50 D. Conclusions: A significant percentage of our population presents with corneal astigmatism > 1.00 D with a shift from WTR (with the rule) to ATR with increasing age. Our findings, in a population that has never been described before, will be helpful to surgeons to enhance surgical techniques, patients to improve visual outcomes, IOL (intraocular lens) manufacturers to make better designs and health agents to optimise resources.